Spectral Lines Exploring the Extreme. (IEEE spectrum)
This paper discusses the advancement of space exploration. According to Bill Stone, 90 percent of the weight of present-day space vehicles, and much of the exorbitant cost of spaceflight, comes from the fuel needed to break through the Earth's atmospheric chains. He is convinced that if you could set up a "water-mining" operation on the moon you could use the water to make liquid oxygen rocket fuel and then port it back to a low-Earth-orbit "gas station," where new kinds of spacecraft could fuel up and take off for the stars.